Analisis Kepatuhan Wajib Pajak Orang Pribadi : Sosialisasi Pajak Sebagai Variabel Moderasi - Dwi Ayu Siti Hartinah; Andi Kusumawati; Syarifuddin Rasyid (Politeknik Ganesha Medan, 2023)
Revenue in the tax sector in 2021 exceeds the target set at the beginning, but is inversely proportional to the receipt of the Annual Tax Return. This study aims to determine the role of tax socialization in moderating the relationship between taxpayer awareness, taxpayer morale, service quality, and system modernization on individual taxpayer compliance. This type of research is quantitative by using a sample of 100 individual taxpayers and using incidental sampling techniques. Data analysis used multiple linear regression analysis and Moderated Regression Analysis. The results of this study indicate that taxpayer awareness and modernization of the system have a positive effect on individual taxpayer compliance, but are not influenced by taxpayer morale and service quality. Socialization as a moderating variable can strengthen the effect of taxpayer awareness and modernization of the system on taxpayer compliance, but weakens the moral influence of taxpayers on individual taxpayer compliance at the North Makassar Tax Service Office, while for service quality it proves that socialization does not moderate the effect of service quality. on the compliance of individual taxpayers at the North Makassar Primary Tax Service Office